2008
DOI: 10.1111/j.1365-3032.2007.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Food and humidity affect sex pheromone ratios in the stink bug, Euschistus heros

Abstract: Male stink bugs, Euschistus heros , only produce the three-component sex pheromone blend consisting of methyl-(2 E ,4 Z )-decadienoate, methyl-2,4,6-trimethyldodecanoate and methyl-2,4,6-trimethyltridecanoate in a constant ratio of 53 : 3 : 44, respectively, when provided with a food source (green beans, Phaseolus vulgaris ). When volatiles are collected from insects with drinking water, humidified air, or under dry conditions, the insects stop producing two components (methyl-2,4,6-trimethyldodecanoate and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Our results give a more precise indication of the critical changes in population dynamics and behaviour of these bugs in the field, that can be used for timing control measures for the key pest, Euschistus heros, with more precision in soybean in the Central Region of Brazil. Because environmental conditions vary in different regions of Brazil, ranging from wet tropical in the north to temperate in the south, a more complete evaluation of this technology in other soybean producing regions is needed to validate or adapt the sex pheromone‐baited trap technology to different environments and stink bug guilds (Moraes et al. 2008b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results give a more precise indication of the critical changes in population dynamics and behaviour of these bugs in the field, that can be used for timing control measures for the key pest, Euschistus heros, with more precision in soybean in the Central Region of Brazil. Because environmental conditions vary in different regions of Brazil, ranging from wet tropical in the north to temperate in the south, a more complete evaluation of this technology in other soybean producing regions is needed to validate or adapt the sex pheromone‐baited trap technology to different environments and stink bug guilds (Moraes et al. 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Our results give a more precise indication of the critical changes in population dynamics and behaviour of these bugs in the field, that can be used for timing control measures for the key pest, Euschistus heros, with more precision in soybean in the Central Region of Brazil. Because environmental conditions vary in different regions of Brazil, ranging from wet tropical in the north to temperate in the south, a more complete evaluation of this technology in other soybean producing regions is needed to validate or adapt the sex pheromone-baited trap technology to different environments and stink bug guilds (Moraes et al 2008b). Additionally, stink bugs in the last years adapted to new crops such as cotton (Willrich et al 2004a(Willrich et al ,b,c, 2005, maize (Townsend and Sedlacek 1986;Á vila and Panizzi 1995) and sunflower (Panizzi and Machado-Neto 1992;Malaguido and Panizzi 1999), so that monitoring technology for stink bugs based on pheromone-baited traps could lead to effective biocontrol strategies that contribute to solving both current and future stink bugs pest problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Moraes et al (2008b) carried out a simple study of E. heros that revealed the importance of understanding the physiology and the behaviour of stink bugs in order to identify the correct sex pheromone blend. When the insects were aerated with food (Phaseolus vulgaris pods), males of E. heros released all three components in the ratio reported by Zhang et al (2003) during seven consecutive days.…”
Section: Euschistus Herosmentioning
confidence: 99%
“…computational automatized systems of capture and analyses of insect behaviour), simple bioassays are often critical to highlight the importance of semiochemical. In addition, it is important to consider how feeding conditions can affect the resulting pheromone blend and activity (Moraes et al 2008b). Determination of biological activity is complicated by the diffi culty of rearing many species in the laboratory, and the resulting changes in behaviour and general biology, even under strict rearing conditions.…”
Section: Continuementioning
confidence: 99%
“…Zhang et al (2003) confirmed the ratio among the three components by previously proposed Aldrich et al, 1994;Borges et al, 1998a) as being: 53 % methyl 2E,4Z-decadienoate, 3% methyl -2,6,10-trimethyldodecanoate and 44 % methyl-2,6, 10-trimethyltridecanoate. Recently, Moraes et al (2008b) carried out a study with E. heros that revealed the importance of understanding the physiology and the behaviour of stink bugs in order to identify the correct sex pheromone blend. When the insects were aerated with food (Phaseolus vulgaris (L.) pods) males of E. heros released all three components in the ratio reported by Zhang et al (2003) during seven consecutive days.…”
Section: Euschistus Herosmentioning
confidence: 99%